The Consequences of modernity - Giddens, Anthony (California Stanford university press, 1990)
In this major theoretical statement, the author offers a new and provoctive interpretation of institutional transformations associated with modernity. What is modernity? The author suggests, ?As a first approximation, let us simply say the following: ?modernity? refers to modes of social life or organization which emerged in Europe from about the seventeenth century onwards and which subsequently became more or less worldwide in their influence.?We do not as yet, the author argues, live in a post-modern world. The distinctive characteristics of our major social institutions in the closing years of the twentieth century suggest that, rather than entering into a period of post-modernity, we are moving into a period of ?high modernity? in which the consequences of modernity are becoming more radicalized and universalized than before. A post-modern social universe may eventualy come into being, but this as yet lies on the other side of the forms of social and cultural organization that currently dominate world history.